1998
DOI: 10.1111/j.1530-0277.1998.tb05928.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Alcohol‐Preferring and Nonpreferring Selectively Bred Rat Lines. II. Operant Self‐Administration in a Continuous‐Access Situation

Abstract: Several rat lines have been developed using preference/nonpreference and daily ethanol intake in the homecage as criteria for selective breeding. Using these lines, behavioral and neural factors that may underlie the genetic basis for the control of ethanol consumption have been examined. In this paper, we report data from eight of these selected lines: the Alcohol-Preferring (P) and Alcohol-Nonpreferring (NP), the Alcohol-Accepting (AA) and Alcohol-Nonaccepting (ANA), and the High Alcohol Drinking (HAD1 and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 25 publications
8
34
0
Order By: Relevance
“…Thus, the alcohol deprivation effect does not appear to be changed in any qualitative manner following dependence, but rather an overall increase in ethanol selfadministration has occurred. The level of ethanol selfadministration observed during protracted abstinence in this population of genetically heterogeneous rats is similar to that observed under similar conditions, but with no deprivation periods, in rats genetically selected for preference for alcohol (Li and McBride 1995;Files et al 1998;Samson et al 1998).…”
Section: Discussionsupporting
confidence: 78%
“…Thus, the alcohol deprivation effect does not appear to be changed in any qualitative manner following dependence, but rather an overall increase in ethanol selfadministration has occurred. The level of ethanol selfadministration observed during protracted abstinence in this population of genetically heterogeneous rats is similar to that observed under similar conditions, but with no deprivation periods, in rats genetically selected for preference for alcohol (Li and McBride 1995;Files et al 1998;Samson et al 1998).…”
Section: Discussionsupporting
confidence: 78%
“…P rats operantly self-administer ethanol intragastrically for its post-ingestive effects (Murphy et al, 1988; Waller, McBride, Gatto, Lumeng, & Li, 1984). P rats will operantly self-administer ethanol using a dipper model, indicating these rats will work for access to ethanol (Files, Samson, Denning, & Marvin, 1998; Murphy, Gatto, McBride, Lumeng, & Li, 1989; Rodd et al, 2003; Rodd-Henricks et al, 2002a, 2002b; Samson, Files, Denning, & Marvin, 1998; Toalston et al, 2008) or sipper tube model (Beckwith & Czachowski, 2014; Bertholomey, Verplaetse, & Czachowski, 2013; Czachowski & Samson, 2002; Samson & Czachowski, 2003; Verplaetse, Rasmussen, Froehlich, & Czachowski, 2012; Verplaetse & Czachowski, 2015) indicating these rats will work for access to ethanol.…”
Section: The P Rat As a Genetic Animal Model Of Alcoholismmentioning
confidence: 99%
“…Ethanol is operantly self-administered, without using fading/adaptation techniques (i.e., P rats work for access to ethanol) (Files et al, 1998; Murphy et al, 1989; Rodd et al, 2003; Rodd-Henricks et al, 2002a, 2002b; Rodd-Henricks, McKinzie, Shaikh, et al, 2000; Samson et al, 1998; Toalston et al, 2008)…”
Section: The P Rat As a Genetic Animal Model Of Alcoholismmentioning
confidence: 99%
“…Also, the animals should be willing to work to obtain the alcohol. Several studies demonstrated that P rats will operant respond even with high workload (fixed-ratio) requirements (Ciccicioppo, Angeletti, & Weiss, 2001; Czachowski & Samson, 2002; Files, Samson, Denning, & Marvin, 1998; Murphy, Gatto, McBride, Lumeng, & Li, 1989; Rodd et al, 2003; Samson, Files, Denning, & Marvin, 1998), achieving estimated BACs in excess of 80 mg% (Rodd et al, 2003). Moreover, recently it has been demonstrated that P rats will exhibit ‘loss-of-control’ binge-like alcohol drinking and attain BACs of 200 mg% on a daily basis (McBride et al, 2013).…”
Section: Criteria For An Animal Model Of Alcoholismmentioning
confidence: 99%